Multifunctional Antenna with Reconfigurable Ultra-Wide Band Characteristics - Verma, Asha; Singh Parihar, Manoj (Společnost pro radioelektronické inženýrství, 2017)
In this paper a multifunctional antenna is presented which offers an ultra-wideband (UWB) operation, an UWB operation with two switchable notches and reconfigurable dual-band operation for WiMAX and WLAN applications, respectively. Total seven functions/states could be achieved from a single antenna using an electronic switching. The antenna uses dual slots on the ground plane to provide a wide bandwidth, ranging from 3.1 GHz to 10.6 GHz. U-Shaped slot and C-Shaped printed strip in the ground are used to generate two notches at 3.6 GHz(WiMAX) and 5.2 GHz (WLAN/ WiFi) bands, respectively. Moreover, four parasitic strips are added in the feed side to make antenna functional at either3.6 GHz or 5.2 GHz or both. Total Five PIN diodes are required to obtain seven operations from the proposed antenna. Seven structures are fabricated and measured to verify the seven states and results are found in good agreement with estimated results obtained from the simulation.
Keywords: Reconfigurable antenna; UWB antenna; C-shaped strip; PIN diode; parasitic strip